Effect of Heat Treatments on the Tensile Properties and Impact Toughness of (6063) Aluminum Alloy - H. Mihdy Jassim, Abdalla (Al-Qadisiyah Journal of Pure Science, 2018)
The effect of heat treatments on the tensile properties and impact toughness of (6063) aluminum alloy have been studied. This study aims to preparing the aluminum alloy (6063) and study the effect of solid solution temperature, ageing time and the ageing temperature on the tensile properties and impact toughness. Preparing alloy samples were homogenized at 560℃ for 2h, then they were solution heat treated at various temperatures (500, 530,560)ºC for 1 h and then rapidly quenched in water at room temperature. The quenched specimens were then aged at (150,175, and 200)ºC for different time periods. The results showed that the best solution treatment temperature is 530ºC and the best ageing temperature is 175ºC. The highest value of the tensile strength and yield stress are (288.6 and 264.5)Mpa respectively, in samples aged at 175ºC for 6h, while the highest value of impact toughness is 24.6J in samples aged at 175ºC for 2h. The specimens with the lowest impact toughness corresponds to the highest value of the tensile strength and yield stress for all ageing temperature